Using the zebrafish model for Alzheimer’s disease research - Newman, Morgan; Ebrahimie, Esmaeil; Lardelli, Michael (Frontiers in Genetics, 2014)
Rodent models have been extensively used to investigate the cause and mechanisms behind Alzheimer’s Disease. Despite many years of intensive research using these models we still lack a detailed understanding of the molecular events that lead to neurodegeneration. Although zebrafish lack the complexity of advanced cognitive behaviors evident in rodent models they have proven to be a very informative model for the study of human diseases. In this review we give an overview of how the zebrafish has been used to study Alzheimer’s Disease. Zebrafish possess genes orthologous to those mutated in familial Alzheimer’s Disease and research using zebrafish has revealed unique characteristics of these genes that have been difficult to observe in rodent models. The zebrafish is becoming an increasingly popular model for the investigation of Alzheimer’s Disease and will complement studies using other models to help complete our understanding of this disease.